REPRESENTASI KEKUASAAN DAN AKSES DALAM SURAT BUNUH DIRI MAHASISWA: ANALISIS WACANA KRITIS MODEL VAN DIJK - Wahyuni, Sri; Mayong; Baharman (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This study aims to describe the representation of power and access in student suicide letters published in online media based on van Dijk's critical discourse analysis approach. This study uses qualitative methods to explore and understand the meaning of student suicide letters in depth. The results show that student suicide letters represent complex practices of power in academic, family, social, and online media environments, with a tendency for authorities to control the thoughts and actions of vulnerable students, thereby triggering suicide. Furthermore, student suicide letters also represent significant inequality of access in communication events, particularly the limited access to communication of students who are victims of bullying, parental conflict, authoritarian parenting, academic pressure, social pressure, psychological pressure, and sexual violence. Student suicide letters also represent inequality of access in online media publications through the low frequency of publications of student suicide letters that contain practices of power in the academic environment and the high frequency of publications of student suicide letters that contain practices of power in the family environment.